CYCLIC RESISTANCE OF LIQUEFIABLE SAND IMPROVED BY BIOPOLYMER SOIL TREATMENT - Park, D. Y.; Bang, J. U.; Im, S. H.; Chang, I. H.; Cho, G. C. (IOP Conference Series: Earth and Environmental Science, 2025)
Various methodologies have been proposed in geotechnical engineering to address seismic liquefaction and mitigate earthquake-induced destruction. Cement, commonly used as a soil stabilizer, is applied through injection techniques to establish stable ground in numerous human endeavors. However, nowadays, biopolymer-based soil treatment (BPST) has emerged as a sustainable geotechnical engineering approach. This study investigates the enhancement of seismic resistance in loose sand prone to liquefaction through the application of polysaccharide biopolymers. Cyclic direct simple shear (CDSS) test was conducted to evaluate the effectiveness of BPST on liquefiable sand ground.